PEMBANGUNAN SEKTOR PERTANIAN MELALUI PENINGKATAN PRODUKTIVITAS PADI: Studi Kasus Pemberian Bantuan Benih Padi Bermutu di Kabupaten Bantul - Rahayu, Astuti (Jurnal Ekonomi & Studi Pembangunan, 2008)
The agricultural sector has an important role in national and regional development. In recent years, this sector has decreased its contribution to GDP. Based on the background of this situation, the author doing research in 2007 with the aim (1) Analizing productivity before and after aid program of good quality rice seed in Bantul Regency. (2) Analyzing income total of farmer he second increase rice productivity can increase the total income of farmersbefore and after aid program of good quality rice seed. Research result showed that, firstly, aid program of good quality rice seed increase the productivity of rice seed has been less than 5 per cent. Second, increasing productivity of rice can increase the total income of farmers.